Statistical literacy and meaningful learning: A dialogical counterpart - Magalhães, Anderson Salvaterra; Nóbrega, Manassés Pereira (Seven Editora, 2023)
In this chapter, we discuss the relevance of David Ausubel's model of meaningful learning for the development of statistical literacy. To this end, a rereading of the model of statistical literacy proposed by Iddo Gal is made from the dialogical perspective of language and culture that emerges from the work of Russian scholars commonly referred to as Bakhtin's Circle. The chapter is structured in three main parts, in addition to the introduction, conclusion and references. In the first, the general lines of the significant learning model are presented. In the second, the dialogical model of statistical literacy is discussed as a counterpart to the learning model described. In the third, the feasibility of such a counterpart is considered by examining BNCC guidelines. The main contribution of this discussion is the demonstration that learning theory, methodology and teaching practice and prescriptions of teaching work do not need to be separated, but can be articulated to enhance the effectiveness of formal education. DOI:https://doi.org/10.56238/ptoketheeducati-050